2012
DOI: 10.1016/s1004-9541(11)60244-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Return Sludge Pre-concentration on Biological Phosphorus Removal in a Novel Oxidation Ditch

Abstract: A pilot-scale, pre-anoxic-anaerobic oxidation ditch was used in this study to treat municipal wastewater with limited carbon source. A novel return activated sludge (RAS) pre-concentration tank was adopted for improving the phosphorus removal efficiency and the effects of RAS pre-concentration ratio were studied. Under the optimal operational condition, the suspended total phosphorus (STP) and the total phosphorus (TP) removal efficiencies were around 58.9% and 63.9% respectively and the effluent 3 4 PO −-P wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…Aiming at lower nitrogen and phosphorus concentrations is essential not only in the design of new plants, but also for upgrading existing wastewater treatment plants. The nitrogen and phosphorus removal efficiencies of conventional active sludge technologies are relatively low and are limited by the carbon source 2 . Several technologies, such as external organic carbon for post-denitrification and recirculation approaches, can be used to solve this problem.…”
Section: Introductionmentioning
confidence: 99%
“…Aiming at lower nitrogen and phosphorus concentrations is essential not only in the design of new plants, but also for upgrading existing wastewater treatment plants. The nitrogen and phosphorus removal efficiencies of conventional active sludge technologies are relatively low and are limited by the carbon source 2 . Several technologies, such as external organic carbon for post-denitrification and recirculation approaches, can be used to solve this problem.…”
Section: Introductionmentioning
confidence: 99%
“…But the effluent quality still meets the standard for small and medium-sized wastewater plant. In addition, it is found through inspection that the total phosphorus concentration of effluent after transformation is reduced by about 0.1 mg/L, which is because the phosphorus release amount of concentrated sludge is higher than that of secondary settling tank sludge and thus the total phosphorus amount into aerobic pond is reduced so as to better remove phosphorus of the system [3,4] Based on experimental research and analysis above, the treatment efficiency of the system will be slightly decreased when concentrated sludge reflow instead of secondary settling tank reflow, but the effluent quality can still meet the standard of secondary emission standard of GB18918-2002. Thus it can be concluded that the technique is feasible.…”
Section: Figure3 System Operation After Concentrated Sludge Reflowmentioning
confidence: 99%
“…It could also be a feedstock in the manufacture of high value products such as polyhydroxylalkanoates [2]. In order to warrant bioavailability of waste activated sludge, suitable pretreatments are needed to disintegrate the hard cell wall of microbes in waste activated sludge to improve substrate solubility and digestibility [3]. Among previously pretreatment methods, alkaline pretreatment has been proved to render relatively high disintegration efficiency [4].…”
Section: Introductionmentioning
confidence: 99%